Analysis of Students Phonological Errors in Pronouncing Vowel Sounds A Case Study of English Learners in Indonesia - Yani Lubis; Rahayu Wulandari; Rana Mai Zuhra; Hawa Alfina Salsabila; Faris Fadillah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study was to find phonological errors that students make when they pronounce vowel diphthongs. Researchers also asked what type of vocal diphthong sound students most often said in tenth grade. Grade X students of the 2021/2022 school year are the subjects of this study. This study used a quantitative descriptive approach. Researchers randomly selected 60 samples from 395 individuals. The tool used is the English Vowel Diphthong word pronunciation test, which includes eight types of English vowel diphthongs with two focus words for each type. Furthermore, a voice recorder is employed to capture the students' pronunciation. Findings showed that students made 339 word mistakes. The pronunciation of X graders shows the most frequent types of vowel diphthong errors: Diphhongs [ɔʊ] with the focus word